Development potential of multi-cropping systems and its influence on agricultural water consumption in the Huang–Huai–Hai River Basin of China - Linghui Li; Qingming Wang; Yong Zhao; Jiaqi Zhai; Haihong Li; Shuying Han; Lichuan Wang; Yunpeng Gui (Agricultural Water Management)
The impact of global warming on the cropping system (CS) has been increasingly emphasized, and it is essential to analyze the changing pattern of the CS and the impact of agricultural water consumption (AWC) for timely adjustment of the crop and water management. This study analyzed the spatial-temporal changes of the actual and potential CS based on the remote sensing and meteorological dataset from 2001 to 2022 to explore the development potentiality of multi-cropping systems (MCS), and adapted the CS change into the Decision Support System for Agrotechnology Transfer model (DSSAT) to simulate the change of evapotranspiration. The results indicated that in the past 22 years, both of the actual and potential CS have shown a trend of transition to MCS with an area of 187.4 thousand km2 and 215.4 thousand km2. The duration of the accumulated temperature above 10°C have prolonged at a rate of 5.2 days decade–1, which shortened the length of growth season (LOS) of the single CS, double CS, triple CS and triple in two years CS by 1.2 days decade–1, 0.8 days decade–1, 2.3 days decade–1, and 0.2 days decade–1, respectively. Warming promoted the transformation to MCS with 64.25 % (35.3 %) potential of area distribution (growth period), and the region with the greatest potential was the mountainous area in the Yellow River Basin. The simulated average evapotranspiration was 491.2 mm per year with an increasing by 30.51 %, and would further increase by 57.28 % after the development of MCS.